Robotic Pollinating Tools for Actinidia Crops - Isabel Pinheiro; Filipe Santos; António Valente; Mário Cunha (Biology and Life Sciences Forum, 2023)
Pollination is a crucial reproductive process that underpins crop yield and quality as well as sustains other ecosystem services essential for our planet’s life. Insects are the largest group of pollinators, particularly bees, handling the pollination of 71 of the 100 crops that contribute to 90% of the world’s food supply. Nevertheless, both biotic and abiotic factors exert considerable influence on bee behaviour, which in turn affects the pollination process. Moreover, the alarming decline in bee populations and other essential insect pollinators presents a major challenge to natural pollination. This work focuses on Actinidia, a dioecious plant, i.e., with female and male flowers on separate plants, which introduces entropy into the pollination phase. In this plant, the number of pollinated seeds directly influences the size of Actinidia fruits (kiwi), so the success of the pollination phase is fundamental. However, natural pollination in Actinidia is mainly entomophilic, i.e., by insects. Hence, the exploration of alternative approaches becomes essential. To address this need, there has been a growing interest in robotic solutions for pollination, which include several tools to perform pollination. This research investigates the existing technologies for conducting artificial pollination procedures. It involves a comprehensive examination of various methods outlined in the literature, thoroughly analysing their strengths and weaknesses. The ultimate objective is to provide valuable insights and guidance to enhance the efficacy of artificial pollination processes